The effect of high oral loading dose of cholecalciferol in non-alcoholic fatty liver disease patients. A randomized placebo controlled trial - Mohamed, Amal Ahmed; Halim, Ahmed Abdel; Mohamed, Sahar; Mahmoud, Seham Mohamed; Bahgat Eldemiry, Eman Mohamed; Mohamed, Rasha Sobh; Shaheen, Mahmoud Maamoun; Naguib, Gina G.; Muharram, Nashwa M.; Khalil, Mona G.; Saed, Salma; Ibrahim, Randa; et al. (Frontiers in Pharmacology, 2023)
Background and Aim: Non-alcoholic fatty liver (NAFLD) is one of the most common progressive metabolic disorders worldwide. There are increasing scientific interests nowadays for the association between vitamin D status and Non-alcoholic fatty liver. Earlier studies have revealed that vitamin D deficiency is highly prevalent in Non-alcoholic fatty liver patients that contributes to poor outcomes. Hence, the present study aimed to assess the efficacy and safety of oral cholecalciferol on Non-alcoholic fatty liver patients. Subjects and Methods: This study was conducted on 140 patients that were randomized either to group 1 that received the standard conventional therapy in addition to placebo or group 2 that received the standard conventional therapy in addition to cholecalciferol during the 4 months study period. Results: At the end of the study group 2 revealed significant decrease (p < 0.05) in the mean serum level of TG, LDL-C, TC, hsCRP as compared to their baseline results and group 1 results. Additionally, a significant improvement in the serum levels of ALT (p = 0.001) was seen in group 2 at the end of the study when compared to group 1. Whereas group 1 did not show any change in these parameters when compared to group 2 and their baseline results. Conclusion: Cholecalciferol was shown to have beneficial effects on serum ALT levels, hsCRP levels and lipid profile of NAFLD patients. Clinical Trial Registration:https://prsinfo.clinicaltrials.gov/prs-users-guide.html, identifier NCT05613192